Utilization of the Kinemaster Application as a Learning Media - Anggra, Rangga; Kashino, Saijo; Vera, Poupot; Jiao, Deng (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2023)
This pandemic has had a considerable impact, disrupting education. However, the implementation of learning must continue. So, for that, teachers are required to be able to make learning videos that are used as practical, exciting learning media so that they are easy to understand. This is so that students can learn as effectively and efficiently as possible in their homes. The purpose of this is so that teachers can improve their ability to make learning media in the form of learning videos using the Kinemaster learning application. Since April 2020, there have been 100,000,000 students ranging from elementary school to tertiary levels have experienced this pandemic, which caused them to be unable to carry out face-to-face learning. Teachers and students are required to adapt to online or online learning. Moreover, of course, teachers are demanded to be more creative, active and innovative in providing materials or teaching materials later; therefore, the ability of teachers to process IT is very much needed in supporting this online learning. Good IT skills and utilization in online learning are required at all levels of education. Still, in online or online learning, videos or creative teaching materials are very much needed, which will take advantage of the sophistication of IT.